The Problem of Online Game Addiction In Elementary School Students Which Hinders Children’s Psychological Development and Handling Strategies - Tania, Dinda; Rahayu, Puji (International Journal of Students Education, 2023)
Along with the times, technological developments are also increasingly developing and have changed many patterns of human life. With the development of technology influencing the world of gaming, in the past many people played traditional games but nowadays it is very rare to find people who play traditional games. As we know, playing games has now become commonplace among society. We can encounter this in everyday life where people play games, especially online games. We can easily find children, teenagers and even adults playing online games using smartphones, this is increasingly supported by current digital developments where it is very easy for someone to access the internet network. In reality, games are able to provide addiction to people who play them, things like this can have different impacts on each person. This article aims to reveal the impact of online games from the perspective of mental health and behavior (psychology). The method used is the literature review method, which is an analysis activity which can take the form of criticism of research being conducted on a specific topic which is part of a scientific field.Based on this research, it can be concluded that students who are addicted to playing online games tend to show changes in behavior in a negative direction, especially in changes in social and emotional attitudes.